Salivary and gingival CXCL8 correlation with periodontal status, periodontal pathogens, and smoking - Frasheri, Iris; Heym, Richard; Ern, Christina; Summer, Burkhard; Hennessen, Till G.; Högg, Christof; Reichl, Franz‐Xaver; Folwaczny, Matthias (Oral diseases, 2022)
Objectives Neutrophil granulocytes have been proposed to play a major role in the mediation of periodontitis‐associated tissue destruction. Their recruitment and activation are regulated by the chemokine CXCL8. This study aimed to delineate the dependency of CXCL8 expression in gingival crevicular fluid (GCF) and saliva on periodontal status, bacterial infection, and smoking, in patients with periodontitis. Methods The study cohort comprised 279 subjects with untreated periodontitis. Probing pocket depth (PPD), gingival recession, bleeding on probing (BOP), plaque index, and bone loss were evaluated. CXCL8 was determined in saliva and GCF using flow cytometry. Results Considering the entire study sample, CXCL8 levels were correlated with the mean PPD (ρ = 0.131; p = 0.029), severity of periodontitis (ρ = 0.121; p = 0.043), BOP (ρ = 0.204; p = 0.001), and smoking (ρ = −0.219; p < 0.0001) in GCF; and, in whole saliva, with mean PPD (ρ = 0.154; p = 0.010) severity of periodontitis (ρ = 0.140; p = 0.020), gender (ρ = 0.178; p = 0.003), and smoking (ρ = −0.156; p = 0.010). Subgroup analysis among non‐smokers revealed significantly higher amounts of CXCL8 in GCF (p = 0.012) and saliva (p = 0.026) comparing subjects with mean PPD ≤3mm and >3mm. Conclusion The current study revealed a strong dependency of CXCL8 expression in GCF on the severity and activity of periodontal disease. Smoking causes a significant reduction in CXCL8 expression in saliva and GCF.